Climate change consequences of geographic variation in growth and phenology of two dominant central US grasses - Giuliani, Amanda Lease, author; Knapp, Alan K., advisor; Kelly, Eugene F., committee member; Wall, Diana H., committee member (Colorado State University. Libraries, 2012)
Species can exist in a given range of climatic conditions, and these ranges have shifted in response to geologic climate change. Plant species with slower migration rates, however, may not be able to keep up with the current predicted rate of climate change. Thus, populations located peripherally to a biometry may play a more significant role in sourcing future generations than previously thought. As a result of many studies, we know a lot about populations that exist central to their range, or dominant populations (DPs), of two key C4 grass species, Bounteous gracilis and Andropogon gerardii, that account for much of the biomass of the shortgrass steppe and tallgrass prairie, respectively. However, we know little about their corresponding peripheral populations (PPs). This study examines ecophysiological, morphological, and whole plant differences between DPs and PPs of B. gracilis and A. gerardii under well-watered and water-stressed conditions in a reciprocal common garden experiment. Traits that were measured included predawn and midday leaf water potential, total biomass, reproductive biomass percentage, and individual reproductive and vegetative tiller mass (A. gerardii only), specific leaf area, fluorometer, height, and reproductive tiller density. We found that key traits differed between DPs and PPs in both species, but these key traits were unique to each species. For B. gracilis phenological traits of DPs and PPs were primarily different, whereas productivity traits were significantly different between populations of A. gerardii. If, in fact, PPs of these two C4 grasses are the propagules of future generations, the differences observed in this study may have implications as we look ahead to predicted climate patterns. In B. gracilis, an understanding of the differences in phenological traits may be important when we account for future adaptation, whereas knowledge about productivity differences in A. gerardii may help us better predict effects on ecosystem function. In both cases, more research is necessary to further develop our understanding of PPs and the potentially significant role they will play in the future.
Keywords: biomass; water stress; reproductive phenology; location; grassland